ANALISIS KECANGGIHAN INVESTOR TERHADAP KETEPATAN REAKSI PASAR DALAM MERESPON PENGUMUMAN DIVIDEN MENINGKAT - Ajat Sudrajat; Lela Hindasah (Jurnal Ekonomi dan Bisnis, 2010)
This research has purpose to analyze the ability of investor to accuracy of market reaction torespond announcement of increasing dividend at Indonesian Stock Exchange. This researchalso examine dividend information indication and accuracy of market reaction. The variablewhich is used to see market reaction is abnormal return, in are side the ability of investor ispromoted by stock holder in institution. The sample which is used in this research is all companieswhich are registrated in Indonesian Stock Exchange is chosen by sampling purposemethod since 2004 to 2006 it is got 127 sample of company. This result of research showsthat increasing dividend announcement doesn’t have information indication, investor is notcorrect to respond decreasing dividend market announcement or Indonesian Stock Exchangehasn’t been efficient in information or in all decisions, and there is no effect or impact fromanalyze of ability investor toward the accuracy of market reaction to respond increasing dividendannouncement.Keywords : Dividend Increase, Information Content, Decisionally Efficient Market, Investor Sophistication, Institutional Ownership.